Detection of Anti-viral Drug Riamilovir and Herbicides in Aqueous Media by Using Pyrene-based Fluorescent Chemosensors - I. S. Kovalev; L. K. Sadieva; O. S. Taniya; D. S. Kopchuk; G. V. Zyryanov; E. N. Ulomsky; V. L. Rusinov; O. N. Chupakhin (Chimica Techno Acta)
Two ethyleneglycol esters of 1-pyrene carboxylic acid were studied as chemosensors for the fluorescence “turn-off” detection of two nitro-containing analytes, such as antiviral drug Riamilovir (Triazavirin ®) and herbicidal agent dinitro-ortho-cresol (DNOC). In both cases the dramatic fluorescence quenching was observed with quenching constants as high as 3·104 M-1 and limits of detection (LOD) as low as 100 ppb.